2019
DOI: 10.1055/s-0039-1695794
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of Cardiac Implantable Electronic Device Data for Older Adults Using Participatory Design

Abstract: Patients with heart failure (HF) are commonly implanted with cardiac resynchronization therapy (CRT) devices as part of their treatment. Presently, they cannot directly access the remote monitoring (RM) data generated from these devices, representing a missed opportunity for increased knowledge and engagement in care. However, electronic health data sharing can create information overload issues for both clinicians and patients, and some older patients may not be comfortable using the technology (i.e., compute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 33 publications
(45 reference statements)
0
38
0
Order By: Relevance
“…RPM programs use various telecommunication channels to collect health datasuch as a symptom surveys, vital signs, or data from wearable sensors-and transmit these data to a healthcare provider in a different location. [15][16][17][18][19] RPM is an attractive care delivery strategy with promise for lower costs, improved convenience, closer monitoring capabilities, and potentially better outcomes. However, data supporting the use of RPM have so far been mixed, with variable results depending on condition and implementation.…”
Section: Background and Significancementioning
confidence: 99%
“…RPM programs use various telecommunication channels to collect health datasuch as a symptom surveys, vital signs, or data from wearable sensors-and transmit these data to a healthcare provider in a different location. [15][16][17][18][19] RPM is an attractive care delivery strategy with promise for lower costs, improved convenience, closer monitoring capabilities, and potentially better outcomes. However, data supporting the use of RPM have so far been mixed, with variable results depending on condition and implementation.…”
Section: Background and Significancementioning
confidence: 99%
“…Previous studies have examined patient preferences and desires in obtaining information from their CIEDs. In one study of seven patients with CRT devices, patients with CRT were asked their preferences and similar to our study stated that they wanted to know about battery life, events, and abnormal pacing when creating a visual dashboard that patients could access . In another study similar to our cohort, the authors found that patients with CIEDs wanted to have information from their devices in electronic or paper form, and having that information did not increase the physician's work load .…”
Section: Discussionmentioning
confidence: 50%
“…Furthermore, designers should be judicious in the use of design techniques, such as personas, which can lead to oversimplification and encourage misleading assumptions about end users [ 82 ]. Other strategies to mitigate incorrect assumptions include conducting more frequent testing or including stakeholders on design teams to challenge assumptions during the design process [ 50 , 71 ].…”
Section: Resultsmentioning
confidence: 99%
“…In these scenarios, individuals were presented with hypothetical situations related to data from a fictitious CIED and asked to think aloud as they made decisions about how to respond. Other formative study methods were a brief observation of a device clinic, meetings with 2 cardiologists, and sharing of findings and design work from 2 recent similar studies on CIED data sharing [ 43 , 50 ].…”
Section: Methodsmentioning
confidence: 99%